The evolution of a manufacturing system at Toyota - Fujimoto, Takahiro (New York Oxford University Press, 1999)
The book traces the development of Toyota's manufacturing system, analyzing its principles, processes, and organizational innovations. Fujimoto highlights how Toyota's approach to production evolved into a lean system that integrates technology, management, and culture to achieve efficiency and competitiveness
Includes bibliographical references and index
Keywords: Công nghệ kỹ thuật ô tô